Description of the Behavior of Chilli Farmers in the Use of Pesticides in Nagari Andiang, Suliki District Fifty City District - Danhas, Yunhendri; Agus Teguh PRIHARTONO (RADINKA JAYA UTAMA PUBLISHER, 2024)
The problem that is often faced in the use of pesticides in the field is the incorrect amount, time, and type of application as a result of the user's lack of knowledge and awareness regarding the correct application of pesticides. From the initial service carried out by researchers, it was seen that several farmers were still not implementing appropriate pesticide applications, such as not wearing personal protective equipment in the form of masks, gloves, and so on. This research aims to describe the behavior of vegetable farmers in pesticide application. This type of research is descriptive and quantitative with a population of 2,361 people and a sample of 48 people. Data was collected from January – March 2024. Data was collected by conducting an initial survey and questionnaire measuring tools. Based on the research conducted, it was discovered that as many as 26 people with a percentage of 54.17% of the sampled chili farmers had low knowledge of pesticide application. As many as 21 people with a percentage of 43.75% of chili farmers had a negative attitude towards pesticide application and as many as 19 people with a percentage of 39.58% had unfavorable attitudes towards pesticide application. It is recommended that the Head of Nagari Wali coordinate with PPL (Field Agricultural Officers) to socialize appropriate and correct pesticide application, so that vegetable farmers maintain their attitude during this time, such as getting used to showering after spraying pesticides and using Personal Protective Equipment (PPE) during pesticide application.